Potret Perilaku Hedonisme Di Kalangan Mahasiswa Prodi BKI UIN Kiai Haji Achmad Siddiq Jember - fikriansyah, fikriansyah; Purnawan, Adam Rizki; Prasetiyo, Fadia Dwi; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This study aims to provide an overview of the portrait of the hedonism lifestyle and the causes of the emergence of hedonism lifestyle factors for students of the Islamic Guidance and Counseling Study Program. This study used a qualitative approach by carrying out activities in certain fields in order to obtain the necessary data and information. Data analysis techniques used in this study are primary data and secondary data. Researchers collected data by reading several book lists, journal literacy, observation, and interviews. The researcher found an interesting thing to explore in this study, namely that we can find a hedonic lifestyle not only in adults who already have their own income but also in students who incidentally still ask money for snacks from their parents, this lifestyle is often found. Therefore, this hedonic lifestyle greatly influences the individual's life during the late adolescent years, in which consumptive actions continuously impact behavior using the principles of satisfaction and pleasure. The results of this study were obtained by interviewing five informants proving that the average hedonistic lifestyle is still attached to them today. In terms of appearance, they are still following trends when going to college, spending weekends by going for walks, often consuming fast food, and oversight prioritizing their desires without seeing the value or benefits as a trigger for a hedonic lifestyle. This should be anticipated or prevented before these behaviors control our lives.